SLP-2 interacts with Parkin in mitochondria and prevents mitochondrial dysfunction in Parkin-deficient human iPSC-derived neurons and Drosophila. (3rd April 2017) - Zanon, Alessandra; Kalvakuri, Sreehari; Rakovic, Aleksandar; Foco, Luisa; Guida, Marianna; Schwienbacher, Christine; Serafin, Alice; Rudolph, Franziska; Trilck, Michaela; Grünewald, Anne; Stanslowsky, Nancy; Wegner, Florian; et al.
Abstract: Mutations in the Parkin gene ( PARK2 ) have been linked to a recessive form of Parkinson's disease (PD) characterized by the loss of dopaminergic neurons in the substantia nigra . Deficiencies of mitochondrial respiratory chain complex I activity have been observed in the substantia nigra of PD patients, and loss of Parkin results in the reduction of complex I activity shown in various cell and animal models. Using co-immunoprecipitation and proximity ligation assays on endogenous proteins, we demonstrate that Parkin interacts with mitochondrial Stomatin-like protein 2 (SLP-2), which also binds the mitochondrial lipid cardiolipin and functions in the assembly of respiratory chain proteins. SH-SY5Y cells with a stable knockdown of Parkin or SLP-2, as well as induced pluripotent stem cell-derived neurons from Parkin mutation carriers, showed decreased complex I activity and altered mitochondrial network morphology. Importantly, induced expression of SLP-2 corrected for these mitochondrial alterations caused by reduced Parkin function in these cells. In-vivo Drosophila studies showed a genetic interaction of Parkin and SLP-2, and further, tissue-specific or global overexpression of SLP-2 transgenes rescued parkin mutant phenotypes, in particular loss of dopaminergic neurons, mitochondrial network structure, reduced ATP production, and flight and motor dysfunction. The physical and genetic interaction between Parkin and SLP-2 and the compensatory potential of SLP-2 suggest a functional epistatic relationship to Parkin and a protective role of SLP-2 in neurons. This finding places further emphasis on the significance of Parkin for the maintenance of mitochondrial function in neurons and provides a novel target for therapeutic strategies.